CONCEPTUAL PROVISIONS OF THE FORMATION OF THE SYSTEM OF MOTIVATION OF THE WORK OF PERSONNEL IN INSTITUTIONS OF HIGHER EDUCATION - MARHASOVA, Viktoriya; KRAVCHYK, Yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the issue of ensuring the effective functioning and development of higher education institutions in Ukraine. In the focus of attention are the issues of strengthening the motivation of the staff of higher education institutions. The purpose of the study is to develop conceptual provisions for the formation of a system of motivation for the personnel of domestic institutions of higher education. It has been proven that the development of Ukrainian higher education institutions is directly dependent on and determined by the quality and efficient work of their staff. In turn, selfless work is determined by its good motivation, and not only material, but also sometimes to a greater extent non-material nature, stimulation and support. It is shown that during the formation of their own personnel motivation management systems, the management of a higher education institution must clearly understand the specifics of the motivation and stimulation of the work of personnel directly in the field and in higher education institutions. Their identification involves a deep disclosure and understanding of specifics in terms of material, non-material and directly deep level personal motivation of scientific and pedagogical personnel and workers. Contributing factors and obstacles that weaken motivation and create a negative attitude towards the work of staff in higher education institutions have been identified. It is indicated that effective work on ensuring a good level of labor stimulation for the staff of domestic institutions of higher education should be implemented according to a clearly defined scenario, consisting of the following areas of increasing the quality and efficiency of work, as an increase in the level of pedagogical skills, the development of scientific activity and self-improvement, the contribution of teachers to the accreditation process, positive actions of the staff in terms of improving the prerequisites for the development of the institution of higher education, its popularization in the professional and social environment.